Original articleAnalysis of the prognostic significance of selected morphological and immunohistochemical markers in ependymomas, with literature review - Żawrocki, Antoni; Iżycka-Świeszewska, Ewa; Papierz, Wielisław; Liberski, Paweł P.; Zakrzewski, Krzysztof; Biernat, Wojciech (Folia Neuropathologica, 2011)
Aim : Ependymal tumours are relatively uncommon primary neoplasms of the central nervous system. Histological criteria distinguishing ependymoma and anaplastic ependymoma are not clear-cut and other parameters are required to allow more precise prognostication in these tumours. We analysed the histological and immunohistochemical features of these tumours (Ki-67, cyclin D1, EGFR, hTERT, Olig2) and correlated them with the clinical outcome. Material and methods : We analysed 39 patients with grade II ependymoma (30) and anaplastic ependymoma (9). Twenty-eight tumours developed in children and the remaining 11 patients were adults with intracranial and intraspinal tumours. Eighteen patients died during the follow-up period. Results and conclusions : Overall survival was reduced significantly for paediatric patients and patients with intracranial tumour. High-grade tumours, increased mitotic index and increased cellularity had an unfavourable influence on survival. Other histological parameters such as nuclear atypia, necrosis and microvascular proliferation did not alter the survival rate. Increased Ki-67 and cyclin D1 indices correlated with worse prognosis. Furthermore, any level of cyclin D1 expression in WHO grade II ependymomas was strongly associated with higher risk of death. No correlation was identified between Olig2, EGFR and hTERT expression and the outcome of the patients.